دور البيئة الأندلسية في شعر ابن خفاجه وأثر الطبيعة فيها دراسة وصفية تحليلية (Comprehensive Journal of Science, 2026)
The study examines the poetry of Ibn Khafaja, focusing on the description of Andalusian nature and the influence of environment on his poetic imagery. It highlights the interplay between natural elements (such as flowers, rivers, and fruits) and human emotions, where the poet blends sensory beauty with deep feelings through vivid imagery. The research also reflects the impact of social and political conditions, especially wars, on shaping some of his poetic themes, including descriptions of weapons. Using an analytical approach, the study reveals the aesthetics of description and confirms that nature was a primary source of his artistic inspiration.
Keywords: Ibn Khafaja, Andalusian nature, poetic description, environment, Andalusian poetry, imagery